The Role of The Cadets' Locus of Control Type in Learning Writing - Lusiana Dewi Kusumayati; Mas Sulis Setiyono; Meita Maharani Sukma; Laila Rochmawati; Fatmawati (International Journal of English Linguistics, Literature, and Education (IJELLE), 2024)
The purpose of this study: This research aims to identify the elements that affect the sort of locus of control cadets have and how important they are in learning to write. To accomplish this, the research's theoretical framework considers the cadets' capacity for writing learning and their position as both internal and external loci of control within the framework of behavioral theory. Method: Researchers employed a form of qualitative descriptive research in their investigation. Observations, surveys, documentation, and interviews gather data. The Constant Comparative Method is used to analyze the data. This research was conducted in the MTU 8A Civil Aviation Polytechnic class of Surabaya. Air Transport Management cadets totaling 25 cadets were used as samples. Findings: As a result of the study, cadets with an internal locus of control type are more capable and eager to engage in writing instruction. Along with their better marks, the cadets appeared to be more engaged. On the other hand, cadets who have an external locus of control type appear to be more passive and have lower scores. Conclusion: It is clear that the locus of control type of cadets plays a significant part in their writing learning.